Safety evaluation and toxicokinetics of repeated inhalation exposure to pegylated interferon α-2b - Ji, Cuifang; Ji, Xunlian; Li, Huan; Wang, Qinfang (Frontiers in Pharmacology, 2025)
This study aimed to evaluate the safety profile and toxicokinetic (TK) characteristics of pegylated interferon α-2b (PEG IFNα-2b) following repeated nebulized inhalation exposure in juvenile Sprague-Dawley (SD) rats, and to establish the no-observed-adverse-effect level (NOAEL) to support its clinical development for pediatric respiratory infections. A total of 190 juvenile SD rats (5–6 days old) were randomized into blank control, low- (126.4 ± 21.8 μg/kg), mid- (384.3 ± 66.9 μg/kg), and high-dose (1,202.4 ± 176.4 μg/kg) groups. Animals received nebulized PEG IFNα-2b via whole-body/nasal inhalation once every 2 days for two consecutive weeks. Assessments included clinical observations, body weight, hematology, coagulation, serum biochemistry, developmental parameters, histopathology, and TK analysis. PEG IFNα-2b was well tolerated at all dose levels, with no treatment-related mortality, clinical signs, or histopathological alterations observed. Systemic exposure increased in a dose-proportional manner; concentrations in the low-dose group were below the lower limit of quantitation (LLOQ), while Cmax values ranging from 0.467 ng/mL (mid-dose, females) to 15.3 ng/mL (high dose, females), and AUC0-last values from 2.18 h·ng/mL (mid-dose, females) to 61.5 h·ng/mL (high dose, females). Accumulation factors ranged from 0.135 to 1.66, indicating no significant drug accumulation. Developmental parameters and histopathological examinations of respiratory tissues revealed no treatment-related abnormalities. The NOAEL was determined to be 1,202.4 ± 176.4 μg/kg, the highest dose tested. Inhaled PEG IFNα-2b demonstrated a favorable safety and TK profile in juvenile rats at doses up to 1,202.4 ± 176.4 μg/kg, supporting its potential as an inhaled antiviral therapy for pediatric respiratory infections.